2018
DOI: 10.1038/s41467-017-02583-0
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-derived exosomal miR-1247-3p induces cancer-associated fibroblast activation to foster lung metastasis of liver cancer

Abstract: The communication between tumor-derived elements and stroma in the metastatic niche has a critical role in facilitating cancer metastasis. Yet, the mechanisms tumor cells use to control metastatic niche formation are not fully understood. Here we report that in the lung metastatic niche, high-metastatic hepatocellular carcinoma (HCC) cells exhibit a greater capacity to convert normal fibroblasts to cancer-associated fibroblasts (CAFs) than low-metastatic HCC cells. We show high-metastatic HCC cells secrete exo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
589
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 764 publications
(634 citation statements)
references
References 46 publications
11
589
0
Order By: Relevance
“…Another study found decreased expression of serum exosomal miR-638 in HCC patients [41] . High miR-1247-3p in serum exosomal levels correlated with lung metastasis, poor overall survival and poor disease-free survival in HCC patients [19] .…”
Section: Exosomal Rna Biomarkersmentioning
confidence: 91%
See 4 more Smart Citations
“…Another study found decreased expression of serum exosomal miR-638 in HCC patients [41] . High miR-1247-3p in serum exosomal levels correlated with lung metastasis, poor overall survival and poor disease-free survival in HCC patients [19] .…”
Section: Exosomal Rna Biomarkersmentioning
confidence: 91%
“…However, depending on the starting material and downstream applications, other methods for the purification and enrichment of HCC-derived exosomes have also been used such as ultrafiltration, size exclusion chromatography (SEC) or the ExoQuick TC method [19,29] . Majority of HCC-derived exosomes have been identified by a combination of different methods including, round or cup shaped morphology by transmission electron microscopy, size of 50-100 nm in diameter by nanoparticle tracking analysis and exosomal surface profiling for markers such the tetraspanins (CD9, CD63, and CD81), heat shock proteins (HSP90 and HSP60), Alix and Tsg101 by immunoblot and flow cytometry [19,20,[29][30][31][32] . Studies have demonstrated high expression of glypican-3 (GPC-3) and AFP, traditional markers of HCC, within the HCC-derived exosomes, thereby confirming the hepatoma-based origin of these exosomes [31] .…”
Section: Isolation and Identification Methods Of Hcc-derived Exosomesmentioning
confidence: 99%
See 3 more Smart Citations